Examination of the composition and microorganisms in the oral microflora with to Immunological parameters identification of Saliva - SABAH, Abdulrazaq Mohammad; NATALIYA, Ikonnikova (International Journal of Computational and Experimental Science and Engineering, 2021)
The oral mucosa is a mucous membrane that connects the lips to the pharyngeal and gastrointestinal mucosa. Its particular properties enable it to function as a gatekeeper, regulating the impact of inhaled and ingested antigens, and the degrees of inflammation and immunological responses tolerated in a normal healthy mouth cavity. The objectives of this study are to: (1) quantification of the composition of the oral micro flora in individuals of 18-50 years old; (2) examination of the oral cavity microorganisms (culture-morphological and microscopic studies); and (3) determination the biochemical parameters (lysozyme concentration, active acidity level) of the oral fluid (saliva). The research evaluated 65 people between the ages of 18 and 50. Swabs from the oral cavity (within the cheeks) were used to inoculate agar media (MPA, Endo medium). Colonies (CFU) on the agar medium's surface were counted and converted to an area of the oral cavity (4 cm2). The oral fluid was collected in the morning, on an empty stomach, before brushing the teeth, into a sterile test tube with a tight-fitting cover. This was done by thoroughly cleaning the individual's mouth with a sterile 0.9% NaCl solution. We used indicator strips of paper with pH ranges of 5.4–7.8, 0.2 steps. Oral fluid centrifuged (2000 rpm for 20 min). Indicator paper was dropped over the supernatant and the pH was calculated using a standard scale. Saliva from patients was collected in 1 ml polyethylene tubes, diluted 1:1 with saline, and centrifuged for 10 minutes at 1500 rpm. We studied the slurry. For this reason, the measurements are done in calibrated test tubes with 3 ml of the investigated lysozyme solution each time. The control is 0.5 M phosphate buffer. The research revealed that those with periodontitis and caries had pH alterations in their saliva. This group's pH was 5.03. Compared to the healthy group, the pH decreased. The results showed that individuals with dental and periodontal issues had substantially lower levels of Lysozyme than healthy people. A severe decrease of nonspecific oral tissue resistance lowers oral fluid resistance to pathogens. Morover, Oral bacteria were all Amoxicillin resistant. Lactobacillus.